Design evolution in total knee replacement: which is the future? - Causero, A.; Di Benedetto, P.; Beltrame, A.; Gisonni, R.; Cainero, V.; Pagano, M. (Acta Biomedica Atenei Parmensis, 2014)
Total knee replacement (TKR) procedures have evolved in the last 40 years to guarantee improvements implants life and an excellent joint function. The goals for the future evolutions are make easier prosthesis implantation and promote precision. The demand for TKR will rise for the life length increase and for the risk factors impact increase. Design evolution in total knee replacement has to satisfy these new necessities: anatomic congruence, range of motion, less material wear and better resistance to the weight bearing and to the stresses. This paper analyzes design evolution, materials development and future purposes in total knee arthroplasty. At the beginning, TKR history is treated; then we compare several prosthetic designs developed during years. At last the paper speak about recent innovations, like CAD (computer aided design) for example, born to reach the most important goal in the future: better TKR design, is the one that better imitate natural knee characteristics, and that is able to integrate it-self with capsule-ligaments and muscle-tendons patient structures.